(3HMQ GdLhGgQs - (3eMeO Hf jhSa , GdWHjH GdgQhis; (3CHh SYjO Hf EHQGgje GdeZQHj GdYdGFjs ((3eMeO MSjf s)
(3ChdgG (B:s
(3hHYO , ajbhd GdYHO GdabjQ GdeMJGL Edi Gddg Gdbhi eMeO Hf jhSa GdWHjH GdYOhi Yde GdWH CTO eeeG jMJGLhfI GdWGdHhf s
(3BNQgG (B:s
(3jfJgi HTQM cdeI (B: (3jhfGf EPG GJNP ef bdGOI hYdbJ ai GdYfb hLYd WhdgG eYJOdkG s
(3QJHgG Ydi MQha GdeYLes
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA WH (B- (3bSe GdcJGH GdChd (B- (3U (B33 s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdWHs